Advantages of Exercise Training In Hypertrophic Cardiomyopathy: Considering risks and benefits - Deddy Tedjasukmana (Jurnal Kardiologi Indonesia, 2019)
Background. Hypertrophic cardiomyopathy (HCM) is one of the most common cardiac genetic disorders. The prevalence of this disease is 1 in 500 live births. It is stated to be the most frequent cause of sudden death in young adults. Therefore, some guidelines recommend to restrict physical activity and exercise. On the contrary, latest data show that active lifestyle and exercise in HCM patient provide significant benefits in cardiovascular function with no significant adverse reactions. Following to that, some experts might be reveal that its benefits might be outweigh risks. Summary. There is a paucity of studies that examine the effectiveness of exercise for HCM. American Heart Association (AHA) and (European Society of Cardiology) ESC established exercise recommendations for HCM individuals based on discussion and consensus of experts. We found three studies that investigate the efficacy of exercise in HCM individuals. Outcomes of our interest were differences in cardiovascular function, quality of life and safety issues. All studies found positive significant differences in main outcomes measure in which the HCM subjects on exercise had better or improved outcomes. None reported adverse reaction such as fatal arrhythmia or sudden death related to exercise. Brief Conclusion. Old belief regarding exercise restrictions on HCM need to be reconsidered, given that at present exercise have been shown to provide significant benefits for reducing cardiovascular risk factors. Nevertheless, exercise in patients with HCM must be specifically considered regarding the risk and benefit. Practicing active lifestyle and exercise on HCM individual is an exciting possibility that need further study. Keywords: hypertrophic cardiomyopathy, exercise training, risks and benefit, physical activity